The Magical Quest: Finding The Perfect Ears and Other Stories: Children’s Picture Books Exploring Children’s Confidence in Their Self-Identity - Aimee Alexis; Dwi Setiawan (Institute of Research and Community Outreach - Petra Christian University, 2024)
Self-esteem has become an important factor for children’s confidence in shaping their self-identity. As children are growing up, they might face questions regarding their self-identity. Self-identity can be divided into ‘natural self’ and ‘environmental self’ which is acquired through external forces. However, there are cases when their identity does not conform with society’s expectation. In these cases, children might find the need to fit in with their surroundings. Therefore, this creative work explores how self-esteem helps embrace one’s identity to develop one’s life goals. Based on Morwenna Griffiths’ theory that was influenced by American Philosopher William James and an American psychologist Carl Rogers, I will explore how one gains self-esteem in order to grasp self-confidence. Unconditional regard and achievement are significant reasons for solutions to the development of self-esteem. My creative work will tell the stories of five characters. The characters will go on a journey to finally be confident in their self-identity. They will regain their self-esteem by realizing their self-worth and value. Children might learn the importance of embracing their identity through my creative work.